2021
DOI: 10.1021/acs.macromol.1c00778
|View full text |Cite
|
Sign up to set email alerts
|

All-Organic Polymer Dielectrics Containing Sulfonyl Dipolar Groups and π–π Stacking Interaction in Side-Chain Architectures

Abstract: Although polymer dielectrics show wide application prospects in electronic and electrical fields, a low relative dielectric constant and a low energy density restrict their rapid developments. To overcome these shortcomings, a strategy is proposed to facilitate orientational polarization through the incorporation of the π−π stacked biphenyl side groups in dipolar polymers. In this study, sulfonyl-containing poly(norbornene)s with and without biphenyl groups were synthesized by ring-opening metathesis polymeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 63 publications
0
44
0
Order By: Relevance
“…To date, multiple strategies have been proposed to increase the e r and E b in order to achieve superior U e , such as single dielectric polymers based on molecular design, [9][10][11][12] single layer or multilayer structure all-organic dielectric polymers blends, [13][14][15][16][17][18][19][20] single layer or multilayer structure polymer-based dielectric nanocomposites with inorganic filler, [21][22][23][24][25][26][27][28] etc. Among these dielectric materials, the polymer-based nanocomposites with ceramic fillers have been extensively studied, originating from combining the merits of high-e r of the ceramic and high-E b of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…To date, multiple strategies have been proposed to increase the e r and E b in order to achieve superior U e , such as single dielectric polymers based on molecular design, [9][10][11][12] single layer or multilayer structure all-organic dielectric polymers blends, [13][14][15][16][17][18][19][20] single layer or multilayer structure polymer-based dielectric nanocomposites with inorganic filler, [21][22][23][24][25][26][27][28] etc. Among these dielectric materials, the polymer-based nanocomposites with ceramic fillers have been extensively studied, originating from combining the merits of high-e r of the ceramic and high-E b of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…142,143 Hence, increasing e r is beneficial to decrease the binding energy of the Frenkel excitons and indeed an advantageous feature for efficient charge transport in organic semiconductors. [144][145][146] Previous studies demonstrated that incorporating cyano functionalities into the p-framework is one of the efficient strategies to enhance e r . 147 According to the energy gap law, dominant exciton-vibronic coupling due to the increased overlap between the ground and excited-state vibrational energy levels at the NIR region exponentially increases the non-radiative deactivation pathways.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The uncovered polymer design strategy introduces a platform for high performance dielectric development for extreme thermal and electric field conditions. In order to improve the ε r and U e of polymer dielectrics, Xu et al (2021) synthesized sulfonyl-containing poly (norbornene)s with and without biphenyl groups (denoted as PBTMD-SO 2 and PTMD-SO 2 ) by ROMP procedure ( Figure 7B ). The ε r of PBTMD-SO 2 with the biphenyl side groups was as high as 11.1 at 25°C and 1 kHz, which was nearly 35% higher than that of PTMD-SO 2 due to the stronger orientational polarization through the incorporation of the π−π stacked biphenyl side groups in polymers.…”
Section: Controllable Synthesis Of All-organic Polymer Dielectricmentioning
confidence: 99%